ANTHROPOMETRIC INDICATORS, BODY MASS INDEX AND THEIR ASSOCIATIONS WITH BODY IMAGE AMONG ADULTS: A SYSTEMATIC REVIEW - Febrianti, Kamila Dwi (Yayasan Education and Social Center, 2024)
Obesity and overweight is still a public health problem that occurs throughout the world. Increasing prevalence of both obesity an overweight globally is linked with poor body image perception. The aim of the study was to evaluate the association between anthropometric indicators, body mass index, and body image in adults from the scientific literature. This systematic reviews using spesific keywords with inclusion and exclusion criteria also restricted for study that publish in the last 5 years in 2017-2022. A systematic review to all five studies that included from study selection based on PRISMA shows the result of there was an association between body mass index as anthropometric indicators in adults and body image with p <0.001. This study findings shows that there was significant statistic value of the assocation between BMI and BI. Both women and men has dissatisfaction with their body image and tend to do under-estimation or over-estimation as they want to have a desired body size then have an ideal body image. Some studies explained that women want to have a thiner body type and men want to have a heavier body type. The dissatsifaction of body image can develop into both mental disorder or other nutrition related diseases. Raising the awareness of good body image can help to reduce long-term consequences of dissatisfaction body size or specific body parts